Hadith #1870 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
We were in the company of Allahâs Messenger (ï·º) on a journey. He said to a man, âGet down and mix Sawiq (powdered barley) with water for me.â The man said, âThe sun (has not set yet), O Allahâs Messenger (ï·º).â The Prophet (ï·º) again said to him, âGet down and mix Sawiq with water for me.â The man again said, âO Allahâs Messenger (ï·º)! The sun!â The Prophet (ï·º) said to him (for the third time) âGet down and mix Sawiq with water for me.â The man dismounted and mix
Grade: Sahih

Hadith #1887 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
I was with the Prophet (ï·º) on a journey, and he observed the fast till evening. The Prophet (ï·º) said to a man, âGet down and mix Sawiq with water for me.â He replied, âWill you wait till it is evening?â The Prophet said, âGet down and mix Sawiq with water for me; when you see night falling from this side, the fasting person should break his fast.â
Grade: Sahih

Hadith #2158 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
as above, mentioning only specific measure.
Grade: Sahih

Hadith #2160 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
as above, saying, âHe should pay the price in advance for a specified measure and for a specified period.â
Grade: Sahih

Hadith #3026 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
We were afflicted with hunger during the besiege of Khaibar, and when it was the day of (the battle of) Khaibar, we slaughtered the donkeys and when the pots got boiling (with their meat). Allahâs Apostle made an announcement that all the pots should be upset and that nobody should eat anything of the meat of the donkeys. We thought that the Prophet (ï·º) prohibited that because the Khumus had not been taken out of the booty (i.e. donkeys); other people said, âHe prohibited eating them for e
Grade: Sahih

Hadith #3590 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
A person asked `Abdullah bin `Umar whether a Muslim could kill flies. I heard him saying (in reply). âThe people of Iraq are asking about the killing of flies while they themselves murdered the son of the daughter of Allahâs Messenger (ï·º) . The Prophet (ï·º) said, They (i.e. Hasan and Husain) are my two sweet basils in this world.â
Grade: Sahih

Hadith #3972 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
`Aisha used to recite this Verse:â âIda taliqunahu bi-alsinatikumâ (24.15) â(As you tell lie with your tongues.)â and used to say âAl-Walaqâ means âtelling of a lie. âShe knew this Verse more than anybody else as it was revealed about her.
Grade: Sahih

Hadith #4044 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
We where afflicted with severe hunger on the day of Khaibar. While the cooking pots were boiling and some of the food was well-cooked, the announcer of the Prophet (ï·º) came to say, âDo not eat anything the donkey-meat and upset the cooking pots.â We then thought that the Prophet (ï·º) had prohibited such food because the Khumus had not been taken out of it. Some others said, âHe prohibited the meat of donkeys from the point of view of principle, because donkeys used to eat dirty things.â
Grade: Sahih

Hadith #4073 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
When Allahâs Messenger (ï·º) performed the `Umra (which he performed in the year following the treaty of Al-Hudaibiya) we were screening Allahâs Messenger (ï·º) from the infidels and their boys lest they should harm him.
Grade: Sahih

Hadith #4109 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
None informed us that he saw the Prophet (ï·º) offering the Duha (i.e. forenoon) prayer, except Um Hani who mentioned that the Prophet (ï·º) took a bath in her house on the day of the Conquest (of Mecca) and then offered an eight rak`at prayer. She added, âI never saw the Prophet (ï·º) offering a lighter prayer than that prayer, but he was performing perfect bowing and prostrations.â
Grade: Sahih

Hadith #5283 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
We participated with the Prophet (ï·º) in six or seven Ghazawat, and we used to eat locusts with him.
Grade: Sahih

Hadith #5419 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
While Hudhaita was at Madaâin, he asked for water. The chief of the village brought him a silver vessel. Hudhaifa threw it away and said, âI have thrown it away because I told him not to use it, but he has not stopped using it. The Prophet (ï·º) forbade us to wear clothes of silk or Dibaj, and to drink in gold or silver utensils, and said, âThese things are for them (unbelievers) in this world and for you (Muslims) in the Hereafter.â â
Grade: Sahih

Hadith #5604 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
While Hudhaifa was at Al-Madain, he asked for water whereupon the chief of the village brought him water in a silver cup. Hudhaifa threw it at him and said, âI have thrown it only because I have forbidden him to use it, but he does not stop using it. Allahâs Messenger (ï·º) said, âGold, silver, silk and Dibaj (a kind of silk) are for them (unbelievers) in this world and for you (Muslims) in the hereafter.â
Grade: Sahih

Hadith #5766 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
I was present when a man asked Ibn `Umar about the blood of mosquitoes. Ibn `Umar said, âFrom where are you?â The man replied. âFrom Iraq.â Ibn `Umar said, âLook at that! he is asking me about the blood of Mosquitoes while they (the Iraqis ) have killed the (grand) son of the Prophet. I have heard the Prophet (ï·º) saying, âThey (Hasan and Husain) are my two sweet-smelling flowers in this world.â
Grade: Sahih

Hadith #6095 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
Whenever a man brought his alms to the Prophet, the Prophet (ï·º) would say, âO Allah! Bestow Your Blessing upon the family of so-and-so.â When my father came to him (with his alms), he said, âO Allah! Bestow Your Blessings upon the family of Abi `Aufa.â
Grade: Sahih

Hadith #6122 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
Whenever somebody brought alms to the Prophet (ï·º) the used to say, âAllahumma Salli âAlaihi (O Allah! Send Your Salat (Grace and Honor) on him).â Once when my father brought his alms to him, he said, âO Allah! Send Your Salat (Grace and Honor) on the family of Abi `Aufa.â
Grade: Sahih

Hadith #6153 - Sahih al-Bukhari - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih al-Bukhari)
Allahâs Messenger (ï·º) asked for Allahâs wrath upon the Ahzab (confederates), saying, âO Allah, the Revealer of the Holy Book, and the One swift at reckoning! Defeat the confederates; Defeat them and shake them.â
Grade: Sahih

Hadith #810 - Sahih Muslim - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih Muslim)
Kaâb b. âUjra met me and said: Should I not offer you a present (and added): The Messenger of Allah (ï·º) came to us and we said: We have learnt how to invoke peace upon you; (kindly tell us) how we should bless you. He (the Holy Prophet) said: Say:â O Allah: bless Muhammad and his family as Thou didst bless the family of Ibrahim. Verily Thou art Praiseworthy and Glorious, O Allah.â
Grade: Sahih

Hadith #969 - Sahih Muslim - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih Muslim)
When the Messenger of Allah (ï·º) raised his back from the rukdâ he pronounced: Allah listened to him who praised Him. O Allah! our Lord! unto Thee be praise that would fill the heavens and the earth and fill that which will please Thee besides them.
Grade: Sahih

Hadith #2444 - Sahih Muslim - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih Muslim)
We were with the Messenger of Allah (ï·º) on a journey. When the sun sank he said to a person: Get down and prepare barley meal for us. Upon this he said: Messenger of Allah, let there be dusk. (He the Holy Prophet) said: Get down and prepare barley meal for us. He (the person) said: There is still (the light of) day upon us. (But) he got down (in obedience to the command of the Holy Prophet) and prepared a barley meal for him and he (the Holy Prophet) drank that (liquid meal) and then said: Whe
Grade: Sahih

Hadith #2446 - Sahih Muslim - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih Muslim)
In this hadith transmitted by one of the narrators (neither these words are found): During the month of Ramadan.â nor his statement:â And the night prevails from that side (the eastern side).â (These words are found in the narration of) Hushaim only.
Grade: Sahih

Hadith #6749 - Sahih Muslim - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sahih Muslim)
â Ali said: Ever since I heard this (supplication) from Allahâs Apostle (ï·º), I never abandoned it. It was said to him, Not even in the night of Siffin (battle of Siffin)? He sad: Yes, not even in the night of Siffin,â
Grade: Sahih

Hadith #3679 - Sunan al-Nasa'i - al-Nu'man bin Bashir ibn Sa'd; Amir al-Sha'bi Ø¹Ø§ÙØ± Ø§ÙØ´Ø¹Ø¨Ù; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Sunan al-Nasa'i)
âAvoid the seven sins that doom one to Hell.â It was said: âO Messenger of Allah, what are they?â He said: âAssociating others with Allah (Shirk), magic, killing a soul whom Allah has forbidden killing, except in cases dictated by Islamic law, consuming Riba, consuming the property of orphans, fleeing on the day of the march (to battlefield), and slandering chaste women who never even think of anything touching their chastity and are good believers.â
Grade:

Hadith #5348 - Sunan al-Nasa'i - Abu Talha Ansari; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; ibn Abbas; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Ubaydullah bin 'Abdullah bin 'Utba Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ØªØ¨Ø© Ø¨Ù ÙØ³Ø¹ÙØ¯; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Sunan al-Nasa'i)
âThe Messenger of Allah was asked how much a woman should let her hem drag. He said: âA hand span.â She said: âBut then it will uncover her (feet).â He said: âA forearmâs length, and no more than that.'â
Grade:

Hadith #19 - Jami' al-Tirmidhi - Aisha bint Abi Bakr; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Mu'adhah bint 'Abdullah ÙØ¹Ø§Ø°Ø© Ø¨ÙØª Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Qatada ÙØªØ§Ø¯Ø©; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Jami' al-Tirmidhi)
âEncourage your Husbands to clean themselves with water, for I am too shy of them, and Allahâs Messenger would do that.â
Grade:

Hadith #165 - Jami' al-Tirmidhi - al-Nu'man bin Bashir ibn Sa'd; Bashyr bin Thabit al-Ansari Ø¨Ø´ÙØ± Ø¨Ù Ø«Ø§Ø¨Øª Ø§ÙØ£ÙØµØ§Ø±Ù; Habib bin Salm al-Ansari ØØ¨ÙØ¨ Ø¨Ù Ø³Ø§ÙÙ Ø§ÙØ£ÙØµØ§Ø±Ù ÙÙÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ja'far bin Iyas; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Jami' al-Tirmidhi)
âI am the most knowledgeable among the people about the prescribed time of this prayer: Allahâs Messenger would pray it when the moon set on the third (of the month).â
Grade:

Hadith #327 - Jami' al-Tirmidhi - Abu Hurairah; Abu Salama bin 'Abdur Rahman Ø£Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Jami' al-Tirmidhi)
Allahâs Messenger said: âWhen the Iqamah is called for Salat do not come to it rushing, rather come to it walking, and while you have tranquility. What you catch of it then pray it, and what you missed of it, then complete it.â
Grade:

Hadith #337 - Jami' al-Tirmidhi - al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; ibn Abbas; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Ubaydullah bin 'Abdullah bin 'Utba Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ØªØ¨Ø© Ø¨Ù ÙØ³Ø¹ÙØ¯; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Jami' al-Tirmidhi)
âI was a companion rider on a female donkey with Al-Fadl. We came while the Prophet and his Companions were performing Salat at Mina.â He said: âWe dismounted from it and joined the row. The donkey then passed in front of them, and this did not invalidate their Salat.â
Grade:

Hadith #561 - Jami' al-Tirmidhi - Aisha bint Abi Bakr; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Urwa ibn al-Zubayr Ø¹Ø±ÙØ© Ø¨Ù Ø§ÙØ²Ø¨ÙØ±; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Jami' al-Tirmidhi)
âThe sun was eclipsed during the time of the Messenger of Allah, so the Messenger of Allah led the people in prayer. He recited a lengthy recitation, then he bowed a lengthy bowing, then he raised his head and recited a lengthy recitation that was less than the first. Then he bowed a lengthy bowing that was less than the first. Then he raised his head and prostrated. Then he did (similar to) that in the second Rakâah.â
Grade:

Hadith #564 - Jami' al-Tirmidhi - al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; ibn Umar; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Salim bin 'Abdullah bin 'Umar Ø³Ø§ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Jami' al-Tirmidhi)
âThe Prophet prayed Salat Al-Khawf, praying one Rakâah with one of the two groups, while the other group was facing the enemy. (When the first group finished they first Rakâah with him), they went and took position (of the second group, facing the enemy). Then the second group came and he led them in another Rakâah, then he said the Taslim to them, while the group proceeded to complete their (second) Rakâah. Thereafter, the first group stood up to finish their (second) Rakâah.â
Grade:

Hadith #620 - Jami' al-Tirmidhi - Abu Ishaq al-Sabay'ai' Ø£Ø¨Ù Ø¥Ø³ØØ§Ù Ø§ÙØ³Ø¨ÙØ¹Ù Ø¹ÙØ±Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly Ø¹Ø§ØµÙ Ø¨Ù Ø¶ÙØ±Ø© Ø§ÙØ³ÙÙÙÙ Ø§ÙÙÙÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Jami' al-Tirmidhi)
the Messenger of Allah said: âI have exempted charity on horses and slaves. So bring charity for silver, one Dirham for every forty Dirham. There is nothing for me (to collect) on one hundred and ninety Dirham, so when it reaches two hundred, then five Dirham of it (are due).â
Grade:

Hadith #771 - Jami' al-Tirmidhi - al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Jami' al-Tirmidhi)
âI witnessed Umar bin Al-Khattab on the Day of Nahr beginning with the Salat before the Khutbah. Then he said: âI heard the Messenger of Allah prohibit fasting on these two days. As for the Day of Fitr, then it is for you to take a break from your fasting, and a celebration for the Muslims. As for the Day of Adha, then eat from the flesh that you have sacrificed.'â
Grade:

Hadith #837 - Jami' al-Tirmidhi - Aisha bint Abi Bakr; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Urwa ibn al-Zubayr Ø¹Ø±ÙØ© Ø¨Ù Ø§ÙØ²Ø¨ÙØ±; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Jami' al-Tirmidhi)
A Hadith similar to no. 835 with a different chain
Grade:

Hadith #991 - Jami' al-Tirmidhi - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat Ø°ÙÙØ§Ù Ø£Ø¨Ù ØµØ§ÙØ Ø§ÙØ³ÙØ§Ù Ø§ÙØ²ÙØ§Øª; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Suhayl bin Abi Salah Ø³ÙÙÙ Ø¨Ù Ø£Ø¨Ù ØµØ§ÙØ (Jami' al-Tirmidhi)
The Messenger of Allah said: âThe best scent is the perfume of musk.â
Grade:

Hadith #1134 - Jami' al-Tirmidhi - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Jabir ibn 'Abdullah; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Muhammad bin 'AR bin Thauban ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø«ÙØ¨Ø§Ù; Yahya bin Abi Kathir ÙØÙÙ Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ± Ø§ÙØ·Ø§Ø¦Ù; Yazid bin Zari' ÙØ²ÙØ¯ Ø¨Ù Ø²Ø±ÙØ¹ (Jami' al-Tirmidhi)
âThe Messenger of Allah prohibited the price of a dog, the dowry of a fornicator, and the payment made to the fortune-teller.â
Grade:

Hadith #1283 - Jami' al-Tirmidhi - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; ibn Umar; Nafie' ÙØ§ÙØ¹ ÙÙÙÙ Ø§Ø¨Ù Ø¹ÙØ±; Ubaidullah bin 'Umar bin Hafs Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù ØÙØµ Ø¨Ù Ø¹Ø§ØµÙ (Jami' al-Tirmidhi)
From his father, that he sought permission from the Prophet (ï·º) to take the wages for cupping and he (ï·º) forbade him from it. He continued asking him and seeking his permission until he said: âUse it to give fodder to your water-carrying camels, and to feed your slaves.â There are narrations on this topic from Rafiâ bin Khadij, Abu Juhaifah, Jabir, and As-Saâib bin Yazid. The Hadith of Muhayyisah is a Hasan Sahih Hadith. This is acted upon according to some of the people of knowled
Grade:

Hadith #1749 - Jami' al-Tirmidhi - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat Ø°ÙÙØ§Ù Ø£Ø¨Ù ØµØ§ÙØ Ø§ÙØ³ÙØ§Ù Ø§ÙØ²ÙØ§Øª; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Suhayl bin Abi Salah Ø³ÙÙÙ Ø¨Ù Ø£Ø¨Ù ØµØ§ÙØ (Jami' al-Tirmidhi)
âThe Messenger of Allah (ï·º) prohibited having images in the house, and he prohibited making them.â He said: There are narrations on this topic from âAli, Abu Talhah, âAishah, Abu Hurairah, and Abu Ayyub. The Hadith of Jabir is a Hasan Sahih Hadith.
Grade:

Hadith #2981 - Jami' al-Tirmidhi - Anas ibn Malik; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Jami' al-Tirmidhi)
from Maâqil bin Yasar that he married his sister to a man among the Muslims during the time of the Messenger of Allah (ï·º). She remained with him as long as she did, then he divorced her once without taking her back until her âIddah elapsed, but they desired each other again. He (Maâqil) said to him: âYou ingrate! I honored you by marrying her to you, then you divorced her. By Allah! She will never be returned to you again.â Allah knew of his heed for her and her need for a husband, s
Grade:

Hadith #3049 - Jami' al-Tirmidhi - Abu al-Juza' - Aws bin 'Abdullah Ø£Ø¨Ù Ø§ÙØ¬ÙØ²Ø§Ø¡ - Ø£ÙØ³ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ±Ø¨Ø¹Ù; ibn Abbas; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Jami' al-Tirmidhi)
from âUmar bin Al-Khattab, that he said: âO Allah! Make the verdict concerning Khamr sufficiently clear for us!â So (the Ayah) in Al-Baqarah was revealed: They ask you concerning Khamr and gambling. Say: âIn them is a great sin (2:219).â So âUmar was called, and it was recited to him, so he said: âO Allah! Make the verdict concerning Khamr sufficiently clear for us!â So (the Ayah) in An-Nisa was revealed: âO you who believe! Approach not As-Salat while you are in a drunken stat
Grade:

Hadith #3926 - Jami' al-Tirmidhi - Abdul Malik bin 'Umayr al-Qabti Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø³ÙÙØ¯ Ø§ÙÙØ¨Ø·Ù; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Jami' al-Tirmidhi)
that the Prophet (ï·º) said: âIndeed Allah has revealed to me that: Whichever of these three places you go to will be the place of your emigration: Al-Madinah, Bahrain, or Qinnasrin.â
Grade:

Hadith #189 - Sunan Ibn Majah - Abu 'Asim al-'Abdani Ø£Ø¨Ù Ø¹Ø§ØµÙ Ø§ÙØ¹Ø¨Ø§Ø¯Ø§ÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Jabir ibn 'Abdullah; Muhammad bin al-Munkdar bin 'Abdullah ÙØÙØ¯ Ø¨Ù Ø§ÙÙÙÙØ¯Ø± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø§ÙÙØ¯ÙØ± (Sunan Ibn Majah)
They all heard the Messenger of Allah say: âComplete the ablution. Woe to the heels because of Hell-fire.â
Grade:

Hadith #208 - Sunan Ibn Majah - Abdul Malik bin 'Umayr al-Qabti Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø³ÙÙØ¯ Ø§ÙÙØ¨Ø·Ù; al-Mndhr bin Jryr bin Abd Ø§ÙÙÙØ°Ø± Ø¨Ù Ø¬Ø±ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¨Ø¬ÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Sunan Ibn Majah)
âThe Messenger of Allah would fall asleep until he was breathing deeply, then he would get up and offer the prayer, and he did not perform ablution.â (Hasan) Tanafisi said: âWaki` said: âShe meant while he was prostrating (he would sleep).'â
Grade:

Hadith #489 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sunan Ibn Majah)
A man among the Ansar sent word to the Messenger of Allah saying: âCome and designate a place in my house where I can perform prayer,â that was after he had become blind. So he went and did that.
Grade:

Hadith #532 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sunan Ibn Majah)
The Prophet used to say: âWhoever performs prayer in congregation at the mosque for forty nights, never missing the first Rakâah of the âIshaâ prayer, Allah will thereby decree for him salvation from the Fire.â
Grade:

Hadith #617 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Jmy' bin 'Umayr bin Afaq Ø¬ÙÙØ¹ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø¹ÙØ§Ù; Sdqh bin Sa'id al-Hnfy ØµØ¯ÙØ© Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØÙÙÙ Ø§ÙÙÙÙÙ (Sunan Ibn Majah)
âI have been commanded to prostrate on seven bones.â
Grade:

Hadith #630 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Abu Sa'id al-Khudri; Ali bin Da'ud,Abu al-Mutawakkal al-Naji Ø¹ÙÙ Ø¨Ù Ø¯Ø§ÙØ¯ Ø£Ø¨Ù Ø§ÙÙØªÙÙÙ Ø§ÙÙØ§Ø¬Ù; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sunan Ibn Majah)
âThe Prophet (ï·º) said to me: âWhen you raise your head from prostration, do not squat like a dog. Put your buttocks between your feet and let the tops of your feet touch the ground.â
Grade:

Hadith #977 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Aisha bint Abi Bakr; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Muhammad bin Khazim al-Darir ÙØÙØ¯ Ø¨Ù Ø®Ø§Ø²Ù Ø£Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙØ¶Ø±ÙØ± (Sunan Ibn Majah)
It was narrated from Anas bin Malik that the Messenger of Allah (ï·º) used to recite Qunut in the Subh prayer, and he used to supplicate in it against one of the Arab tribes for a month, then he stopped doing so.
Grade:

Hadith #1026 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Amir al-Sha'bi Ø¹Ø§ÙØ± Ø§ÙØ´Ø¹Ø¨Ù; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; ibn Abbas; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sunan Ibn Majah)
It was narrated from âAmr bin Shuâaib, from his father, from his grandfather, that the Prophet (ï·º) did not pray before or after the âEid prayer.
Grade:

Hadith #1121 - Sunan Ibn Majah - Bkyr bin al-Akhns Ø¨ÙÙØ± Ø¨Ù Ø§ÙØ£Ø®ÙØ³; ibn Abbas; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Jabbarh bin al-Mghls al-Hmany Abu Ø¬Ø¨Ø§Ø±Ø© Ø¨Ù Ø§ÙÙØºÙØ³; Mujahid bin Jabir ÙØ¬Ø§ÙØ¯ Ø¨Ù Ø¬Ø¨Ø±; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Sunan Ibn Majah)
âThe Messenger of Allah (ï·º) said to âAbbas bin âAbdul-Muttalib: âO âAbbas, O my uncle, shall I not give you a gift, shall I not give you something, shall I not tell you of something which, if you do it, will expiate for ten types of sins? If you do them, Allah will forgive you your sins, the first and the last of them, the old and the new, the unintentional and the deliberate, the minor and the major, the secret and the open, ten types of sin. Pray four Rakâah, and recite in each R
Grade:

Hadith #1128 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; ibn Abbas; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ikrama Ø¹ÙØ±ÙØ© (Sunan Ibn Majah)
It was narrated from Abu Bakrah that when the Prophet (ï·º) heard news that made him happy, or for which one should be happy, he would fall down prostrate in gratitude to Allah, the Blessed and Exalted.
Grade:

Hadith #1231 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; ibn Umar; Lahaaq bin Hameed bin Sa'id ÙØ§ØÙ Ø¨Ù ØÙÙØ¯ Ø¨Ù Ø³Ø¹ÙØ¯ Ø£Ø¨Ù ÙØ¬ÙØ² (Sunan Ibn Majah)
âI heard the Messenger of Allah (ï·º) say: âWhen you offer the prayer for the deceased, supplicate sincerely for him.ââ
Grade:

Hadith #1388 - Sunan Ibn Majah - Abu Dharr al-Ghaffari; al-Walid bin 'Abdur Rahman Ø§ÙÙÙÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø§ÙØ¬Ø±Ø´Ù; Da'ud bin Abi Hnd Ø¯Ø§ÙØ¯ Ø¨Ù Ø£Ø¨Ù ÙÙØ¯; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Jubayr bin Nufayr al-Hadrami; Muslimh bin 'Alqama al-Mazny ÙØ³ÙÙØ© Ø¨Ù Ø¹ÙÙÙØ© Ø§ÙÙØ§Ø²ÙÙ (Sunan Ibn Majah)
âWhen you see the new crescent, fast, and when you see it, stop fasting. If it is cloudy then calculate it (as thirty days).â Ibn âUmar used to fast one day before the new crescent was seen.
Grade:

Hadith #1530 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat Ø°ÙÙØ§Ù Ø£Ø¨Ù ØµØ§ÙØ Ø§ÙØ³ÙØ§Ù Ø§ÙØ²ÙØ§Øª; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Suhayl bin Abi Salah Ø³ÙÙÙ Ø¨Ù Ø£Ø¨Ù ØµØ§ÙØ (Sunan Ibn Majah)
âWhenever a man brought Sadaqah to the Messenger of Allah, he would bless him. I brought him the Sadaqah of my wealth and he said: âAllhumma, salli ala ali abi awfa(O Allah! Send blessing upon the family of Abu Awfa).â â
Grade:

Hadith #1656 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Abu 'Uthman al-Nahdi Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙÙ - Ø£Ø¨Ù Ø¹Ø«ÙØ§Ù Ø§ÙÙÙØ¯Ù; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Usamah ibn Zayd (Sunan Ibn Majah)
âI never looked at or I never saw the private part of the Messenger of Allah.â â
Grade:

Hadith #1839 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Aisha bint Abi Bakr; al-Aswad bin Yazid Ø§ÙØ£Ø³ÙØ¯ Ø¨Ù ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³ Ø§ÙÙØ®Ø¹Ù; al-Hasan bin 'Ubaidullah Ø§ÙØØ³Ù Ø¨Ù Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø±ÙØ©; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ibrahim al-Nakha'i Ø¥Ø¨Ø±Ø§ÙÙÙ Ø§ÙÙØ®Ø¹Ù (Sunan Ibn Majah)
âWhoever swears an oath and says In shaâ Allah, if he wishes he may go ahead and if he wishes he may not, without having broken his oath.â
Grade:

Hadith #1955 - Sunan Ibn Majah - Abu Barda bin Abi Musa al-Asha'ari Ø£Ø¨Ù Ø¨Ø±Ø¯Ø© / Ø§ÙØØ§Ø±Ø« Ø¨Ù Ø£Ø¨Ù ÙÙØ³Ù Ø§ÙØ£Ø´Ø¹Ø±Ù; Abu Ishaq al-Sabay'ai' Ø£Ø¨Ù Ø¥Ø³ØØ§Ù Ø§ÙØ³Ø¨ÙØ¹Ù Ø¹ÙØ±Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Abu Musa al-Asha'ari; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Sunan Ibn Majah)
âI heard Malik Abu Safwan bin âUmairah, say: âI bought a pair of trousers from the Messenger of Allah (ï·º) before the Hijrah, and he weighed it for me and allowed more.ââ
Grade:

Hadith #1998 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Suhayl bin Abi Salah Ø³ÙÙÙ Ø¨Ù Ø£Ø¨Ù ØµØ§ÙØ (Sunan Ibn Majah)
Zaid, Abu âAyyash, the freed slave of Bani Zuhrah, told him that he asked Saâd bin Abu Waqqas about buying wheat with barley. Saâd said to him: âWhich of them is better?â He said: âWheat.â He told him not to do that and said: âI heard the Messenger of Allah (ï·º) being asked about buying fresh dates with dried dates, and he said: âDo fresh dates decrease in weight when they become dry?â They said: âYes.â So he told them not to do that.â
Grade:

Hadith #2199 - Sunan Ibn Majah - Abdul Malik bin 'Umayr al-Qabti Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø³ÙÙØ¯ Ø§ÙÙØ¨Ø·Ù; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Raba'i bin Harash bin Jahsh Ø±Ø¨Ø¹Ù Ø¨Ù ØØ±Ø§Ø´; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Sunan Ibn Majah)
We used to give land in return for food at the time of the Messenger of Allah (ï·º), and some of my paternal uncles came to them and said: âThe Messenger of Allah (ï·º) said: âWhoever has land, he should not rent it out for a set amount of food.â
Grade:

Hadith #2325 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; ibn Umar; Jmy' bin 'Umayr bin Afaq Ø¬ÙÙØ¹ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø¹ÙØ§Ù; Sdqh bin Sa'id al-Hnfy ØµØ¯ÙØ© Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØÙÙÙ Ø§ÙÙÙÙÙ (Sunan Ibn Majah)
âIf a slave steals, then sell him, even for half Price.â â
Grade:

Hadith #2666 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abdullah bin Fyrwz Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ±ÙØ² Ø§ÙØ¯Ø§ÙØ§Ø¬; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Sa'id bin Abi 'Aruba Ø³Ø¹ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¹Ø±ÙØ¨Ø©; Uthman bin Muhammad (Sunan Ibn Majah)
âWhoever does not have sandals let him wear leather socks, and let him cut them to below the ankle.â
Grade:

Hadith #2788 - Sunan Ibn Majah - Abdul Malik bin 'Umayr al-Qabti Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø³ÙÙØ¯ Ø§ÙÙØ¨Ø·Ù; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Rfa'h bin Shdad Ø±ÙØ§Ø¹Ø© Ø¨Ù Ø´Ø¯Ø§Ø¯; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Sunan Ibn Majah)
It was narrated from Ibn âAbbas that the Messenger of Allah (ï·º) used to stone the Pillars when the sun had passed its zenith, to the extent that, as soon as he finished stoning them, he would pray Zuhr.
Grade:

Hadith #2851 - Sunan Ibn Majah - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; ibn Umar; Nafie' ÙØ§ÙØ¹ ÙÙÙÙ Ø§Ø¨Ù Ø¹ÙØ±; Ubaidullah bin 'Umar bin Hafs Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù ØÙØµ Ø¨Ù Ø¹Ø§ØµÙ (Sunan Ibn Majah)
âWhoever is in Makkah when the month of Ramadan comes, and he fasts it and prays at night as much as he can, Allah will record for him (reward equivalent to that for) one hundred thousand months of Ramadan observed elsewhere. For each day Allah will record for him (reward equivalent to that for) freeing a slave, and for each day (reward equivalent to that for) providing a horse in the cause of Allah, and for every day merits and for every night merits.â
Grade:

Hadith #2892 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sunan Ibn Majah)
It was narrated from Jabir bin âAbdullah that the Messenger of Allah (ï·º) ordered that a piece from every camel that had been slaughtered be brought and placed in a pot, then they ate from its meat and drank some of the broth.
Grade:

Hadith #2908 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sunan Ibn Majah)
âO Messenger of Allah, some people bring us meat, and we do not know whether the Name of Allah has been mentioned over it or not.â He said: âSay: Bismillah and eat.â They were new in Islam.
Grade:

Hadith #3349 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sunan Ibn Majah)
âThe sandals of the Prophet (ï·º) had two thongs.â
Grade:

Hadith #3420 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat Ø°ÙÙØ§Ù Ø£Ø¨Ù ØµØ§ÙØ Ø§ÙØ³ÙØ§Ù Ø§ÙØ²ÙØ§Øª; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Suhayl bin Abi Salah Ø³ÙÙÙ Ø¨Ù Ø£Ø¨Ù ØµØ§ÙØ (Sunan Ibn Majah)
âI asked the Messenger of Allah(ï·º) about a lost camel that comes to my cisterns that I have prepared for my own camels â will I be rewarded if I give it some water to drink? He said: Yes, in every living being there is reward.'â
Grade:

Hadith #3522 - Sunan Ibn Majah - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Aisha bint Abi Bakr; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Muhammad bin Khazim al-Darir ÙØÙØ¯ Ø¨Ù Ø®Ø§Ø²Ù Ø£Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙØ¶Ø±ÙØ± (Sunan Ibn Majah)
âThe Messenger of Allah(ï·º) said: Qul Huwa Allahu ahad is equivalent to one third of the Quran.â
Grade:

Hadith #3524 - Sunan Ibn Majah - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ Ø¨Ù ØªØ¯Ø±Ø³ Ø£Ø¨Ù Ø§ÙØ²Ø¨ÙØ±; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Sunan Ibn Majah)
âShall I not tell you of the best of your deeds, the most pleasing to your Sovereign, those that raise you most in status, that are better than your gold and silver, or meeting you enemy (in battle) and you strike their necks and they strike your necks?â They said: â WHat is that, O Messenger of Allah?â He said: âRemembering Allah(Dhikr).â
Grade:

Hadith #3538 - Sunan Ibn Majah - Abdur Rahman bin Abi Layla Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø£Ø¨Ù ÙÙÙÙ; Hudhayfah ibn al-Yaman; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; Ja'far bin Iyas; Mujahid bin Jabir ÙØ¬Ø§ÙØ¯ Ø¨Ù Ø¬Ø¨Ø±; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Sunan Ibn Majah)
the Prophet (ï·º) used to say: âAl-hamdu lillahi âala kulli hal. Rabbi aâudhu bika min hali ahlin-nar (Praise is to Allah in all circumstances, O Allah, I seek refuge with You from the situation of the people of Hell).â
Grade:

Hadith #3736 - Sunan Ibn Majah - Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨; ibn Umar; Uthman bin al-Mughira al-Thqfy Ø¹Ø«ÙØ§Ù Ø¨Ù Ø§ÙÙØºÙØ±Ø© Ø§ÙØ«ÙÙÙ ÙÙÙØ§ÙÙ Ø£Ø¨Ù Ø§ÙÙØºÙ; Wadah bin 'Abdullah al-Yashkari ÙØ¶Ø§Ø Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ§ÙØ© (Sunan Ibn Majah)
âWhile the Messenger of Allah (ï·º) was sitting in the mosque, a woman from Muzainah (tribe) entered, trailing her garment in the mosque. The Prophet (ï·º) said: âO people, tell your women not to wear their adornments and show pride in the mosque, for the Children of Israel were not cursed until their women wore adornments and walked proudly in their places of worship.ââ
Grade:

Hadith #3871 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø§ÙÙØ®ØªØ§Ø±; Abu Hurairah; Ibn Abi al-Shuwarab ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ´ÙØ§Ø±Ø¨ (Sunan Ibn Majah)
âWretched is the slave of the Dinar and the slave of the Dirham, and the slave of velvet and the slave of the Khamisah.* If he is given, he is pleased and if he is not given, he does not fulfill (his oath of allegiance).â
Grade: